A novel tests set-up for validation of connector models subjected to static and impact loadings. (December 2021) - Reil, Matthias; Morin, David; Langseth, Magnus; Knoll, Octavian
Highlights: Numerical simulations can be used to design components for precision testing. Novel test setup, focus the loading on the connections under various loading modes. Static and dynamic testing of hybrid connections (SPR and adhesive bonding). Up to date diagnostic techniques enable validation of connection models. Accurate representation of hybrid connections through idealized numerical models. Abstract: A novel test set-up is presented for validation of hybrid connector models between steel and aluminium components subjected to static and impact loading. The proposed components consisted of two hat profiles in steel and aluminium joined by adhesive bonding combined with self-piercing riveting. The geometry of the components was determined by numerical simulations in order to focus the behaviour on the connections under normal and shear dominated loading. The chosen components were tested under static and dynamic loading conditions in a 3-point bending setup. Different displacement measurement techniques were applied to reveal the specimens behaviour, including digital image correlation.Test results were applied to validate idealized numerical models of adhesive and self-piercing riveting connections.